Site characterization mapping in New England using fundamental frequency (f0) - Pontrelli, Marshall. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Civil Engineering.; Advisor: Laurie Baise.; Committee: John Ebel, Juan Pestana, Jon Lamontagne, and Jack Ridge.; Keywords: Civil engineering, Geological engineering, and Geophysical engineering.